Nigerian Film Industry and Screenplay Text: Historical and Linguo-Socio-Cultural Symbiosis - j. Baghana; Т. G. Voloshina (Научный диалог, 2023)
The issue of the development of the Nigerian film industry and the specifics of the screenplay text as a reflection of the linguocultural picture of the world is considered. The question is raised about identifying the linguo-socio-cultural features of the screenplay text formed during the contact interaction of British English and the indigenous languages and cultures of Nigeria. It is proved that the text of the Nigerian film script has all the key textual categories, like the texts of British and American films, but in the refraction of the Nigerian linguistic culture. The scientific novelty of the study is determined by the derived new properties of the Nigerian screenplay text in the process of linguocultural adaptation of British English to the realities of Nigerian culture. The author’s development of a model of linguocultural adaptation of the Nigerian screenplay text is presented and its unique properties at the level of vocabulary and grammar are revealed. Particular attention is paid to the aspect of the sociolinguistic differentiation of the Nigerian society and the identification of errors in the dialogic communication of the characters depending on their belonging to the sociolinguistic type — acrolect, mesolect, basilect. The results obtained can be used for researchers in the field of the theory of language contacts in the field of communicative syntax.